2011
DOI: 10.3324/haematol.2010.036814
|View full text |Cite
|
Sign up to set email alerts
|

Surface molecule CD229 as a novel target for the diagnosis and treatment of multiple myeloma

Abstract: The online version of this article has a Supplementary Appendix. BackgroundTo date, multiple myeloma remains an incurable malignancy due to the persistence of minimal residual disease in the bone marrow. In this setting, monoclonal antibodies against myelomaspecific cell surface antigens represent a promising therapeutic approach, which is however hampered by a lack of appropriate target structures expressed across all pathogenic myeloma cell populations. We, therefore, investigated functionally relevant immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 37 publications
3
65
0
1
Order By: Relevance
“…11 Here, we have shown that CD229 is homogenously expressed on the malignant plasma cells across all plasma cell dyscrasias while it shows much lower levels of expression on the other leukocyte subpopulations present in the patients' bone marrow. We have also shown that CD229 is preferentially expressed on those bone marrow-infiltrating plasma cells showing an abnormal, more "malignant" phenotype as indicated, for example, by expression of CD56.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…11 Here, we have shown that CD229 is homogenously expressed on the malignant plasma cells across all plasma cell dyscrasias while it shows much lower levels of expression on the other leukocyte subpopulations present in the patients' bone marrow. We have also shown that CD229 is preferentially expressed on those bone marrow-infiltrating plasma cells showing an abnormal, more "malignant" phenotype as indicated, for example, by expression of CD56.…”
Section: Discussionmentioning
confidence: 93%
“…11 In particular, the unintended targeting of normal T and NK cells by CD229-specific CAR T cells may affect strategies for their use as a therapeutic option. However, recent data suggested that the targeting of T cells by cross-reactive CARs may not be as problematic as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Some interesting findings have shown that CD229 is constantly present on the surface of human bone marrow PCs, being expressed in myeloma cell lines, multiple myeloma (MM) and monoclonal gammopathies of uncertain significance (MGUS). Thus, CD229 has been proposed as a novel target for the diagnosis and treatment of MM [3]. …”
Section: Tablementioning
confidence: 99%
“…Ly9 is also expressed in virtually all chronic lymphocytic leukemias (CLL) (12). Its expression is not lost during B cell differentiation into plasma cells, and it is highly expressed on multiple myeloma cells (13). Ly9 has four extracellular Ig-like domains, and as has been shown with other SLAMF members, the N-terminal Ig domain of Ly9 mediates homophilic adhesion (14).…”
Section: Introductionmentioning
confidence: 99%